BioRock: new experiments and hardware to investigate microbe–mineral interactions in space. Issue 4 (24th July 2017) - Loudon, Claire-Marie; Nicholson, Natasha; Finster, Kai; Leys, Natalie; Byloos, Bo; Van Houdt, Rob; Rettberg, Petra; Moeller, Ralf; Fuchs, Felix M.; Demets, René; Krause, Jutta; Vukich, Marco; et al.
Abstract: In this paper, we describe the development of an International Space Station experiment, BioRock. The purpose of this experiment is to investigate biofilm formation and microbe–mineral interactions in space. The latter research has application in areas as diverse as regolith amelioration and extraterrestrial mining. We describe the design of a prototype biomining reactor for use in space experimentation and investigations on in situ Resource Use and we describe the results of pre-flight tests.